Frontend de una aplicación multiplataforma que fomente el autoaprendizaje en el alumnado de la ESPAM MFL utilizando estrategias de gamificación - Tuárez Anchundia, Ariel Alexander (2023)
This curricular integration project arises from the need to promote the self-learning of ESPAM MFL students, for this, the main objective was defined, to develop the frontend of a multiplatform application driven by gamification techniques, a product that has the name "Gamivity”. The agile development methodology known as "Extreme Programming" (XP) was used, which is divided into four fundamental phases: planning, design, development and testing. This methodology allowed an iterative and incremental approach in the development of the project, facilitating adaptation to changes and the continuous delivery of value throughout the process. In the planning phase, an exploratory analysis of similar applications that use gamification in the playstore was carried out, as well as studies regarding the main gamification strategies used in educational applications; in the design phase, the Software Requirements Specification document was prepared based on the IEEE 830 standard, likewise the sketches of the different user interfaces were established, as well as the behavior of the minigames and activities; in the development phase, the solution was programmed, using the Flutter multiplatform framework and the REST services of the backend of the "Gamivity" platform. Finally, the unit, acceptance and integration tests were carried out, which validated the correct functioning of the different components of the application. In this way, the development of the frontend of a multiplatform application that promotes self-learning in ESPAM MFL students using gamification strategies was obtained as a result.